Seychelles : Third Review Under the Stand-By Arrangement, Financing Assurances Review, Cancellation of the Stand-By-Arrangement, and Request for an Extended Arrangement-Staff Report; Staff Statement, Press Release on the Executive Board Discussion; and Statement by the Executive Director for Seychelles. (IMF Staff Country Reports; Country Report, 2010)
This paper discusses key findings of the Third Review Under the Stand-By Arrangement for Seychelles. The program is on track, and macroeconomic stabilization has advanced rapidly. The authorities continue to implement the program with a high degree of ownership and success. All quantitative performance criteria (PC) and structural benchmarks at end-September 2009 were met. The structural reform effort is progressing well. Key progress has been made on public financial management, notably through the treasury single account. The 2010 budget features a much improved and complete presentation of government finance.